Local and farmers' knowledge matters! How integrating informal and formal knowledge enhances sustainable and resilient agriculture - Šūmane, Sandra; Kunda, Ilona; Knickel, Karlheinz; Strauss, Agnes; Tisenkopfs, Talis; Rios, Ignacio des Ios; Rivera, Maria; Chebach, Tzruya; Ashkenazy, Amit (Journal of rural studies, 2018)
The widespread transformations in farming practices during recent decades across many parts of Europe – increased capital intensity, scale enlargement, specialization, intensification and mechanization have been accompanied by a quite dramatic shift towards more standardized agricultural information and knowledge. Previous research reveals that transition towards more sustainable agriculture requires a new knowledge base, with new content and forms of knowledge and new processes of learning. In this paper, we explore the relevance of informal farmer knowledge and learning practices in constructing alternative pathways in sustainable agriculture and strengthening agricultural resilience. It is based on 11 case studies carried out within the international RETHINK research programme. The cases reveal the diversity of knowledge sources and learning forms that farmers use and the particular role of farmers’ experience-based knowledge. Farmers greatly value local experiential knowledge as they see it as having practical, personal and local relevance. Given the limitations of more standardized information and knowledge, and the urgent need for a transition towards more sustainable and resource-efficient practices, we argue that the potential of local farmer knowledge is not being optimally used and that a better integration of various forms of knowledge is needed. We identify several ways in which different kinds of knowledge can be integrated. For the individual farmer this can be done by synthesising knowledge from different sources. It can also be done through farmer networking – whether or not facilitated by formal agricultural knowledge institutions, through collaboration between farmers and researchers as knowledge co-generators, and through multi-actor knowledge networks that bring together participants from various fields. We conclude that the dynamic contexts, complexity and the local specificity of the current challenges facing agriculture and the many roles it is being asked to fulfil require more inclusive, flexible modes of governing the generation, integration and sharing of knowledge. All stakeholders, including farmers, need to be recognised as equal co-authors of knowledge generation, and all kinds of knowledge, both formal and informal, need be brought together in innovation processes. Knowledge networking and multi-actor knowledge networks that facilitate knowledge exchanges, joint learning and the generation of new more integrated solutions, are crucial if agriculture is to become sustainable and resilient. •Sustainable and resilient agriculture is knowledge-intensive and requires location-specific knowledge.•Farmers rely considerably on informal knowledge and learning modes.•Local farmers' knowledge strengthens sustainability and resilience, yet remains undervalued.•Knowledge networking and transdisciplinarity facilitate integration of diverse knowledge.